Ø¹Ø²Ù„ Ø¹Ø§Ø«ÙŠØ§Øª Ø§Ù„Ù…ÙƒÙˆØ±Ø§Øª Ø§Ù„Ø¹Ù†Ù‚ÙˆØ¯ÙŠØ© Ø§Ù„Ø°Ù‡Ø¨ÙŠØ© Ø§Ù„Ù…Ù‚Ø§ÙˆÙ…Ø© Ù„Ù„Ù…Ø«ÙŠØ³ÙŠÙ„ÙŠÙ† ÙˆØ£Ù…ÙƒØ§Ù†ÙŠØ© Ø§Ø³ØªØ®Ø¯Ø§Ù…Ù‡Ø§ ÙÙŠ Ø§Ù„Ø¹Ù„Ø§Ø¬ Ø§Ù„ØÙŠÙˆÙŠ Ø¶Ø¯ Ù…Ø¶ÙŠÙÙ‡Ø§ - Hind Fieq Abd Alamer; Ziad M. F. AL-Khozai (Al-Qadisiyah Journal of Pure Science, 2017)
This study involved the collection of 100 samples of different clinical situations for patients of different ages, reviewed the hospital Diwaniyah general education for the period from November 1220 to February 2013 to investigate Staphylococcus aureus resistance to anti Methicillin. 50 have been diagnosed with the isolation of S.aureus included 18 isolates originating from burns 11 isolates from the cysts and 18 isolates from wounds 2 isolation of lactation and the isolation of one of the ear.I tested the sensitivity of the isolates to 16 antibiotics, all isolates were resistant to antibiotics Penicillin G and Ampicillin and Amoxicillin Clavulinic acid and by (100%), while the resistance to antibiotics Ceftriaxone and Cefotaxime and Cephalothin rates (77.2%) and (72.7%) and (74.2%) respectively, while the resistance to the anti Erythromycin rate (69.6%),while the resistance of the two anti Gentamicin and Amikacin was proportions (53%) and (48.4%), respectively, while the decreased resistance to antibiotics Clindamycin and Tetracyclin and Chloramphenicol to (48.4%) and (37.8%) and (34.8%), respectively, while the resistance to antibiotics Ciprofloxacin and Imipenem and Meropenem was very low, as was (1.5%) and (3.0%) and (21.2%), respectively, while all isolates were sensitive to anti Vancomycin by (100%).Been investigating the bacterium Staphylococcus aureus resistance to anti AlMethicillin Methicillin Resistant Staphylococcus aureus (MRSA) in all S. aureus isolates adult (50) and the isolation of 30 isolates showed a positive result using the center CHROMagar MRSA.Through this study was to isolate different types of bacteriophagology depending on the difference in the form of Qatar and the gap of the total 100 samples of sewage and studied various properties.Managed phage bacterial molecules adsorption capacity for the time amounted to a maximum of between 3-5 minutes and has a stillness about 7.5 ± o.5 minutes, Phage molecules that have been highly effective when tested in the resolution of bacterial cells, and that the effectiveness amounted to a maximum of up to two hours of mixing Phage molecules with an implanted bacterial decomposition, while the total time was 5 hours. The calculated data showed that the volume of blowouts was about 125 ± 18 (phage molecule / cell) at the time of an estimated 5 ± 30 minutes. The results also showed that the unarmed T. bacteria MRSA isolated from sewage were more sensitive to injury Balaathi of isolates isolated from clinical cases. That the effectiveness of molecules Phage reached the highest level of effectiveness in the middle neutral between 6 and 0.5 and 8.5 pH 9 after the event begins to decline. The effectiveness of the molecules Phage has not changed much when temperatures are up to 45°C, while there was a decrease extrusive growing in this event when it was lap bacteriophagology temperatures of 50°C and 60°C and reached the greatest impact on the effectiveness of bacteriophagology at a temperature of 70°C was the end point of effectiveness Phage at a temperature of 70°C after 8-10 minutes. Lower standard of molecules Phage appeared in 6 hours incubation period and increased the standard increase temperatures down to optimal levels.The results of the DNA extracted from the type of DNA he appeared in one package meaning it is a single chromosome is divided molecular weight (300 Dalton .(